Comparative Study of Maharah Qiro’ah Learning Through Prayer Readings in Malaysia and Indonesia Elementary Schools: English - Rahmat, Firda Fauzya; Radif Khotamir Rusli,; Mutiara, Fikni (Tatsqifiy: Jurnal Pendidikan Bahasa Arab, 2025)
This study discusses the learning of maharah qiro'ah (Arabic reading skills) through prayer recitations in two elementary schools: Sungai Merab Luar Elementary School in Malaysia and Amaliah Elementary School in Indonesia. The main objective is to identify the learning approaches used and compare their similarities and differences. This study uses a qualitative method with a comparative analysis approach Bereday . Data were collected through interviews, documentation, and observation, and analyzed using triangulation of sources and methods. The results show that elementary schools in Malaysia use a gradual Islamic Education Curriculum and focus on basic introduction, while elementary schools in Indonesia adopt the Merdeka Curriculum with a more systematic and interactive approach. There are similarities and differences in methods, media, strategies, as well as environmental and student factors that influence learning in both schools.